Successful Retroviral Gene Transfer of Simian Virus 40 T Antigen and Herpes Simplex Virus-Thymidine Kinase into Human Hepatocytes - Naoya Kobayashi M.D., Ph.D.; Hirofumi Noguchi; Karen A. Westerman; Takamasa Watanabe; Toshihisa Matsumura; Toshinori Totsugawa; Toshiyoshi Fujiwara; Philippe Leboulch; Noriaki Tanaka (Cell Transplantation, 2001)
Current clinical reports have indicated that hepatocyte transplantation (HTX) could be used in patients with liver failure and in children with liver-based metabolic diseases. One of the major limiting factors of HTX is a serious shortage of donor livers for hepatocyte isolation. To address this issue, we immortalized adult human hepatocytes with a retroviral vector SSR#69 expressing the genes of simian virus 40 large T antigen and herpes simplex virus-thymidine kinase simultaneously. One of the resulting clones, NKNT-3, grew steadily in chemically defined serum-free medium without any obvious crisis and showed the gene expression of differentiated liver functions. Under the administration of 5 μM ganciclovir, NKNT-3 cells stopped proliferation and died in in vitro experiments. We have established a tightly regulated immortal human hepatocyte cell line. The cells could allow the need for immediate availability of consistent and functionally uniform cells in sufficient quantity and adequate quality.